Antywartości. Konceptualizacja zła w świadomości językowej Polaków i Rosjan - Barbara Rodziewicz (Studia Rossica Posnaniensia)
The present article is an attempt at establishing a way of understanding the term evil as well as characterizing all the phenomena the term encompasses in communities of Polish and Russian students. The author analyses the results of a Free Word Association Test on the material of associative dictionaries.